Residents' perception of pilgrimage tourism sustainability In mountain regions: The St. James Primitive Way Case in Asturias - Magadán Díaz, Marta; Rivas García, Jesús Israel (Sustainable Development of Mountain Territories, 2023)
The main objective of this research is to evaluate the changes in local conditions in the economic, sociocultural, and environmental perspectives in association with the development of the pilgrimage tourism sector from the perspective of the residents of mountain areas through which the St. James Primitive Way passes in Asturias. The specific objective is to evaluate the sociodemographic factors of such perceived changes using Logit regression analysis and seemingly unrelated regression analysis. The results obtained indicate the following: firstly, that, although the residents positively value the non-overcrowding of pilgrims on this primitive jacobean route, their perceptions detect some negative changes in the surroundings of Pola de Allande and Grandas de Salime related to noise pollution, the management, and treatment of waste and the state of the Jacobean route; secondly, residents perceive the conservation and condition of the St. Jacques' route as poor and that there are no improvements in infrastructure and public transport services; Finally, thirdly, the impacts of the Primitive Way, today, although positive, are very modest and are mainly limited to two sectors: hospitality and accommodation, which are the activities where employment is being generated. Residents surveyed perceive positive changes in employment and income distribution and negative changes in the evolution of the prices of goods and services and the cost of living.
Восприятие жителями устойчивости паломнического туризма в горных регионах: «Примитивный путь Святого Иакова» в Астурии
Keywords: Asturias; regression analysis; SUR analysis; survey method; sustainable tourism; tourists' perception; Scopus